Assessment of cytotoxic artemisinin and its derivatives as DNA damaging inducing agents in triple-negative breast cancer cells - Mkhwanazi, Ntando (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
In developing countries, including South Africa, breast cancer is the primary cause of cancer-related deaths among women. TNBC (triple-negative breast cancer) is an aggressive breast cancer subtype that is more prevalent in women of African descent. This subtype lacks the key receptors, namely the estrogen receptor (ER-), progesterone receptor (PR-), and human epidermal growth factor receptor 2 (HER2-) that are the basis of successful targeted therapies for other subtypes of the disease. To date, there are no effective, standardized targeted therapies for TNBC. Artemisinin is an anti-malarial drug and numerous derivatives of the compound have been developed to improve the potency and solubility of the parent compound. Artemisinin and its derivatives have gained attention as potential anti-cancer agents; however, such studies have not yet progressed to clinical trials and the precise mechanism of action of these compounds is yet to be fully explained. In this study, artemisinin, and its known derivative artesunate, as well as a novel derivative, WHN11, were investigated as DNA damage-inducing agents in TNBC. WHN11 was found to be the most potent of the three compounds, displaying an IC50 of 3.20 Î¼M against HCC70 cells, artemisinin displayed an IC50 of 214.70 Î¼M and artesunate displayed an IC50 of 25.48 Î¼M. The compounds were less toxic to the MCF12A non-cancerous cells, with IC50 values 298.30, 87.53, and 8.35 Î¼M for artemisinin, artesunate, and WHN11, respectively, and displayed selectivity indices of 1.39, 3.44 and 2.61 Î¼M for artemisinin, artesunate, and WHN11, respectively. In silico and in vitro studies revealed that the artemisinin compounds bind to DNA through the minor groove. While all three compounds were able to bind to DNA, a comet assay revealed that only artemisinin and artesunate, and not WHN11, were able to cause DNA damage compared to the vehicle control, DMSO. Finally, a topoisomerase I (TOPO I) enzyme assay demonstrated that while the compounds appeared to display a degree of inhibition of TOPO I, as evidenced by a downward shift in the plasmid band on the agarose gel, they were not able to fully inhibit the enzyme to return the plasmid to the supercoiled conformation. In addition, combination studies revealed that artemisinin, artesunate, and WHN11 acted synergistically in combination with camptothecin, but displayed either an additive (artemisinin) or antagonistic (artesunate and WHN11) relationship when used in combination with etoposide. In conclusion, artemisinin, its known derivative artesunate, and novel and highly toxic derivative WHN11, all bind to DNA via the minor groove, however only artemisinin and artesunate, and not WHN11, cause DNA damage, indicating a potentially different mechanism of action of the three artemisinins. All three compounds act synergistically with camptothecin, which suggests interference with topoisomerase activity, partially supported by slight inhibition of TOPO I activity, and could indicate either direct inhibition of the enzyme or interference with enzyme function by competitive binding to the DNA. Further studies could help explore alternate DNA damage assays, to validate these findings, and the effect of the compounds on TOPO II activity could also be assessed.
Keywords: Breast Cancer; Artemisinin; DNA damage; Antineoplastic agents; Breast Cancer Treatment